A case of fibrillary glomerulonephritis necessitating multidisciplinary care - George Nishimura; Manasvi Koppana; Richard Smith (Clinical Medicine)
Introduction: Fibrillary glomerulonephritis (FGN) is a rare glomerular disorder associated with significant morbidity. This case report describes a 58-year-old man presenting with renal insufficiency, metabolic derangement and subsequent cardiac failure. The patient’s clinical course was marked by recurrent hospitalisations because of fluid overload with associated dyspnoea, likely secondary to progressive left ventricular dysfunction, as demonstrated by serial echocardiograms. This case highlights that FGN may be associated with rapidly progressive heart failure, indicating that extrarenal manifestations may be key features in non-amyloid-mediated fibrillary glomerulopathies. Results: A 58-year-old man presented to the emergency department of a district general hospital complaining of nausea and vomiting. The patient had a medical background of asthma, anxiety, depression and migraines. Routine blood tests were performed, which showed urea of 67.1 mmol/L, creatinine of 2,502 μmol/L, haemoglobin of 64 g/L and potassium of 7.5 mmol/L; on blood gas analysis, pH was reported as 7.286. The patient was subsequently managed under critical care for haemofiltration, and a native kidney biopsy was performed, which demonstrated negative Congo-Red staining in all renal compartments (Fig 1); importantly, DNAJB9 staining was positive in glomeruli (Fig 2). DNAJB9 immunohistochemistry has recently been identified as a sensitive and specific hallmark for FGN and has not been reported in amyloidosis.1 The patient also suffered from symptoms and signs consistent with heart failure, and, therefore, echocardiography was performed, which demonstrated moderate to severely reduced left ventricular systolic function and a visually estimated ejection fraction of 35–40%. A broad range of potential diagnoses were considered in this case; amyloidosis was considered unlikely, given negative Congo-Red staining, viral screens were negative, Fabry’s screen was negative, serum ACE was normal and ANA levels were normal, suggesting limited scope for autoimmune differentials. Given these investigation findings and the DNAJB9 positivity on biopsy, the most likely diagnosis was concluded to be FGN. Conclusion: The patient re-presented over the subsequent months with dyspnoea and evidence of fluid overload. Serial echocardiograms demonstrated pleural effusions and that the patient’s left ventricular ejection fraction reduced substantially from 40% in the penultimate weeks of the patient’s first admission to <20% in a span of 6 months. This case underscores the multisystemic nature of FGN with renal, cardiac and pulmonary complications. Previously, endomyocardial biopsy in a case of fibrillary/immunotactoid glomerulopathy with progressive cardiac failure demonstrated patchy fibrosis2; however at this time, DNAJB9 had not been identified as an excellent tissue marker of FGN. Immunotactoid glomerulopathy has been reported in association with progressive cardiac failure,3 likely indicating the prominence of extrarenal sequelae as presenting signs of non-amyloid-mediated glomerulopathies. Both fibrillary and immunotactoid glomerulopathy are both characterised by the presence of randomly arranged, Congo Red-negative fibrils; however, FGN is widely but not universally recognised to be distinct from immunotactoid glomerulopathy.4 In this case, while a multidisciplinary approach was used to manage the clinical and psychological manifestations, an evidence-based treatment regimen is still needed for FGN.